Theoretical Issues of the Formation of the Industrial Policy of Enterprises - Lochan, S. A.; Fedyunin, D. V.; Bezpalov, V. V.; Petrosyan, D. S. (International Journal of Economics and Financial Issues, 2015)
The present article specifies the basic principles and components of the social and economic policy of enterprises. Structuring of components enabled the authors to formulate the main directions according to their activity profile and to provide a more detailed definition of the industrial policy of enterprises. The authors showed the nature of the impact of the industrial policy on the industrial complex of enterprises, its importance and relevance; the main problems are also outlined. The specific ways and opportunities for the solution of these problems, formulated by the authors, made it possible to offer the scheme of the main components of the concept of the formation of the industrial policy at enterprises and to define the key purpose, which in turn made it possible to specify tasks, requirements and restrictions when forming the industrial policy of enterprises at the present stage. The research conducted in the present article and the concept of industrial policy offered by the authors are regarded as the instrument of strategic management, the corrective model of the management system of enterprises taking into account the opportunities for strategic development and the influence of sectoral and regional policy, as well as science, which confirms the relevance of this subject. Keywords: social economic policy, external and internal components, infrastructure, industrial complex, concept of formation. JEL Classifications: L52, L53, M14